Ověřování vlastností betonů s nanočásticemi - Pacltová, Klára (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Diplomová práce se zabývá posouzením vlivu přídavku uhlíkových nanočástic do cementových kompozitů. Teoretická část diplomové práce je zaměřena na rešerši informací o uhlíkových nanočásticích, přesněji o uhlíkových nanotrubičkách a grafen oxidu. Jsou zde shrnuty metody dispergace uhlíkových nanotrubiček a jejich vliv na cementové kompozity. Praktická část navazuje na rešerše z části teoretické. V první fázi byla ověřena správná technika dispergace grafen oxidu. Následně byly ověřeny účinky grafen oxidu na mechanické vlastnosti cementových malt. V závěrečné fázi diplomové práce byly poznatky získané z předchozí části ověřeny na betonových vzorcích.

This diploma thesis deals with the influence of addition of carbon nanoparticles on cement composites. The theoretical part of the diploma thesis is focused on the research of information about carbon nanoparticles, more precisely about carbon nanotubes and graphene oxide. There are summarized methods of dispersing carbon nanotubes and their effects on cement composites. The practical part follows the theoretical part of the research. In the first phase, the correct technique of graphene oxide dispersion was verified. Subsequently, the effects of graphene oxide on the mechanical properties of cement mortars were verified. In the final phase of the diploma thesis, the knowledge gained from the previous part was verified on concrete samples.
Verification of properties of concretes with nanoparticles
Keywords: nanočástice; uhlíkové nanotrubičky; grafen oxid; redukovaný grafen oxid; dispergace; cementový kompozit; beton; nanoparticles; carbon nanotubes; graphene oxide; reduced graphene oxide; dispersion; cement composite; concrete